Experimental Study and Mathematical Modelling of Zinc Removal by Reverse Osmosis Membranes - Al-Alawy, Ahmed Faiq; Salih, Miqat Hasan (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
In this study, aromatic polyamide reverse osmosis membranes were used to remove zinc ions from electroplating wastewater. Influence of different operating conditions such as time, zinc concentration and pressure on reverse osmosis process efficiency was studied.  The experimental results showed, concentration of zinc in permeate increase with increases of time from 0 to 70 min, and flux of water through membrane decline with time. While, the concentrations of zinc in permeate increase with the increase in feed zinc concentration (10–300 mg/l), flux decrease with the increment of feed concentration. The raise of pressure from 1 to 4 bar, the zinc concentration decreases and the flux increase. The highest recovery percentage was found is 54.56% for reverse osmosis element, and the highest rejection of zinc was found is 99.49%. Experimental results showed that the concentrations of zinc ion in permeate was lower than the permissible limits (i.e. ˂ 10 ppm). A mathematical model describing the process was investigated and solved by using MATLAB PROGRAM. Theoretical results were consistent with the experimental results approximately 90%.